Language interference in elt writing class - Muliyana Muliyana; Muhammad Zuhri Dj.; Andi Muhammad Yauri (Institut Agama Islam Negeri (IAIN) Bone, 2021)
This research about The Effect of Using Language Interference in ELT Writing Class at The Tenth Grade of Athirah Bone. It is intended to find out two problems of writing. The first problem is the types of errors made by the students in students’ writing skills of the tenth grade of Athirah Bone. This research used a qualitative method by implementing interview. The sample consisted of 9 students from Athirah Bone. The result shows that the students’ perception of the types of students’ errors in writing consist of five perceptions. The first is students’ perceptions relate to the feeling. The second is students’ perceptions relate with the first language’ influence students in mastering the second language. The third is the students’ perception relates to the students’ experiences and kinds of interferences that students have made on writing. The fourth is the students’ perception relates to the factors that cause students to do interfere in writing. The last is about the students’ perception of the difficulties in writing. The second problem is the factors that cause students to do interfere in writing through the observation, it is found that there are four factors that make the students of the tenth grade of Athirah Bone do interfere in writing. The first is do not master spelling. The second is still confused about using the article. The third is Missing using singular and plural nouns. The last is missing space.